Tilt Test as a Primary Non-Invasive Method for Testing Cardiac Autonomic Nervous System Function in Patients with Vasovagal Syncope - Tymoshenko, Dmytro A.; Derkach, Mykola V.; Topchii, Alina V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction Syncope is a sudden, brief loss of consciousness with rapid spontaneous recovery, caused by transient global cerebral hypoperfusion. Among various causes of syncope, the most common are reflex mechanisms, particularly vasovagal syncope (VVS) [1]. At present, the tilt test is the most widely used non-invasive method for testing the cardiac autonomic nervous system. Tilt test results are verified using the modern VASIS classification, which distinguishes three types of vasovagal syncope. Aim The aim of this study was to determine the role of the tilt test in assessing the cardiac autonomic nervous system and its influence on the selection of treatment strategies for patients with vasovagal syncope. Materials and Methods A retrospective analysis was conducted on data from 40 patients who presented to the Amosov National Institute of Cardiovascular Surgery with recurrent syncope and had a positive tilt test result. Among those examined were 30 men and 10 women, with a mean age of 37.8 ± 11.6 years (with an age range of 15-69 years). The tilt test was performed according to the classical Italian protocol. Following the test and confirmation of vasovagal syncope, each patient was assigned an appropriate treatment strategy – ranging from conservative management to invasive interventions. Results. All 40 patients had a positive tilt test result, confirming the vasovagal origin of syncope. This high rate of positive responses likely reflects careful preselection of candidates for potential invasive treatment. Syncope occurred in 36 patients (90 %) during the nitroglycerin provocation phase and in 4 patients (10 %) during the passive tilt phase. The mean time to syncope in the passive tilt phase was 10.8 ± 2.1 minutes (range: 8-15 minutes), while in the nitroglycerin phase it was 4.2 ± 2.3 minutes (range: 1-13 minutes). A cardioinhibitory type was identified in 24 patients (60 %), a mixed type in 11 (28 %), and a vasodepressor type in 5 (12 %). Treatment strategies were determined jointly with the patients. Fourteen individuals with recurrent syncope and a pronounced vagal component underwent catheter ablation of parasympathetic ganglionated plexi, with no procedural complications and complete resolution of vagally mediated sinus node dysfunction. Another 10 with the cardioinhibitory type opted for conservative therapy. Among those with the mixed type, six underwent cardioneuroablation, while the remaining five were managed conservatively. Invasive interventions for the vasodepressor type remain uncommon [10,12], and these patients were treated conservatively. Conclusions The tilt test plays a crucial role in diagnosing vasovagal syncope by assessing the cardiac autonomic nervous system. Accurate classification of the vasovagal syncope type using the VASIS classification directly influences subsequent treatment decisions. According to numerous contemporary studies, invasive treatments demonstrate the greatest effectiveness in patients with the cardioinhibitory type of vasovagal syncope.